Hydrogen sulfide biochemistry and interplay with other gaseous mediators in mammalian physiology - Giuffrè, Alessandro (2019)
Hydrogen sulfide (H2S) has emerged as a relevant signaling molecule in physiology, taking its seat as a bona fide gasotransmitter akin to nitric oxide (NO) and carbon monoxide (CO). After being merely regarded as a toxic poisonous molecule, it is now recognized that mammalian cells are equipped with sophisticated enzymatic systems for H2S production and breakdown. The signaling role of H2S is mainly related to its ability to modify different protein targets, particularly by promoting persulfidation of protein cysteine residues and by interacting with metal centers, mostly hemes. H2S has been shown to regulate a myriad of cellular processes with multiple physiological consequences. As such, dysfunctional H2S metabolism is increasingly implicated in different pathologies, from cardiovascular and neurodegenerative diseases to cancer. As a highly diffusible reactive species, the intra- and extracellular levels of H2S have to be kept under tight control and, accordingly, regulation of H2S metabolism occurs at different levels. Interestingly, even though H2S, NO, and CO have similar modes of action and parallel regulatory targets or precisely because of that, there is increasing evidence of a crosstalk between the three gasotransmitters. Herein are reviewed the biochemistry, metabolism, and signaling function of hydrogen sulfide, as well as its interplay with the other gasotransmitters, NO and CO.